THE INFLUENCE OF AUDIT TENURE, PROFITABILITY AND FINANCIAL VIABILITY ON AUDIT DELAYS WITH AUDIT QUALITY AS A MODERATOR : EVIDENCE FROM ASEAN - Tanggor Sihombing; Bayana Putri Khairunisa (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This research aims to analyze the effect of auditor tenure, profitability, and solvency on the possibility of audit delay in real estate companies’ period 2020-2023 listed on S&P Capital IQ. This research uses a sample criterion of companies that provide complete financial statement data on real estate companies in Indonesia, the Philippines, Malaysia, Thailand and Singapore. The research uses quantitative approach with regression analysis. Research showed that audit delays are negatively affected by auditor tenure and profitability. Solvency also has a negative effect on audit delay. The implication of this analysis is the importance of the level of profit in reducing the risk of audit delay which can increase efficiency in the company's financial reporting, as well as considering the length of the relationship between the company and the auditor.